2013
DOI: 10.1186/1471-2180-13-198
|View full text |Cite
|
Sign up to set email alerts
|

A structural comparison of lipopolysaccharide biosynthesis loci of Legionella pneumophila serogroup 1 strains

Abstract: BackgroundThe lipopolysaccharide (LPS) is the major immuno-dominant antigen of all Legionella species including L. pneumophila. Its diversity is the basis for the classification of L. pneumophila into serogroups and monoclonal subgroups and is thought to be involved in strain specific virulence. The understanding of the genetic basis of the LPS-antigen is incomplete. Thus, we analyzed the genetic locus involved in LPS-biosynthesis of L. pneumophila serogroup 1 (Sg1) strains with the focus on strain specific ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 60 publications
0
13
0
Order By: Relevance
“…In order to investigate the genetic basis determining the serogroup type of the strain PtVFX/2014 (serogroup 1), we analyzed the nucleotide sequences of two genes ( wzt and wzm ) belonging to the lipopolysaccaride (LPS) cluster of L. pneumophila 39 , since these loci were found to be good genetic markers for discriminating L. pneumophila serogroups 34 35 . In this regard, phylogenetic reconstructions over individual gene alignments were performed through MEGA5 by using the neighbor-joining method with bootstrapping (1000 replicates) and the Kimura-2-parameter for distance estimates.…”
Section: Methodsmentioning
confidence: 99%
“…In order to investigate the genetic basis determining the serogroup type of the strain PtVFX/2014 (serogroup 1), we analyzed the nucleotide sequences of two genes ( wzt and wzm ) belonging to the lipopolysaccaride (LPS) cluster of L. pneumophila 39 , since these loci were found to be good genetic markers for discriminating L. pneumophila serogroups 34 35 . In this regard, phylogenetic reconstructions over individual gene alignments were performed through MEGA5 by using the neighbor-joining method with bootstrapping (1000 replicates) and the Kimura-2-parameter for distance estimates.…”
Section: Methodsmentioning
confidence: 99%
“…Genome analyses with Geneious version 9 (10) revealed that the previously described ~30-kb unstable genetic element (11) was absent from strain OLDA, but a pP36-like element (12) is maintained. A deletion of the lag-1 O-acetyltransferase also corroborates its monoclonal antibody-2 (mAb2 = mAb3/1) negative phenotype (13, 14). Strain OLDA is sequence type 1 (ST1) (15) and highly similar (≥98.5%) to the ST1 L. pneumophila reference strain Paris (NC_006368) (16).…”
Section: Genome Announcementmentioning
confidence: 64%
“…Mapping to the L. pneumophila Philadelphia 1 reference genome (Accession number: AE017354) revealed that 39% (n=673) of the k-mers aligned to a region of the genome spanning between loci lpg0748 and lpg0781 representing an 18 kb cluster of genes involved in LPS biosynthesis and modification ( Fig. 2) (Petzold et al, 2013). A total of 22 genes in this cluster each had at least one significantly enriched k-mer that mapped to it: lpg0751, lpg0752, lpg0755, lpg0758, lpg0759, lpg0760, lpg0761, lpg0762, lpg0766, lpg0767, lpg0768, lpg0769, lpg0771, lpg0772, lpg0773, lpg0774, lpg0775, lpg0777 (lag-1), lpg0778, lpg0779, lpg0780 and lpg0781 (Fig.…”
Section: Genome-wide Association Analysis Of L Pneumophila Reveals Gmentioning
confidence: 99%